An insight into real and average structure from diffuse X‐ray scattering – a case study. Issue 4 (16th July 2016) - Chodkiewicz, Michał Leszek; Makal, Anna; Gajda, Roman; Vidovic, Dragoslav; Woźniak, Krzysztof
Abstract : Diffuse X‐ray scattering from an organic salt has been analysed including modeling of the local structure, explaining relationships between symmetry and extinction patterns, and assessing the sensitivity of the calculated diffuse scattering to the model of the average structure. Abstract : Two‐dimensional diffuse X‐ray scattering from an organic salt [ N ‐(3‐(2, 6‐dimethylanilino)‐1‐methylbut‐2‐enylidene)‐2, 6‐dimethylanilinium chloride, C21 H27 N2 + Cl − ] was interpreted with the help of an analytical model of diffuse scattering. An analysis of the relationship between symmetry and diffuse scattering for the studied system has been undertaken. The symmetry of the system explains the extinction pattern, taking the form of curves, on the diffuse scattering planes. We have also tested the relationship between the average structure model and scattering intensities. Two models, differing in their representation of overlapping atoms, were used. In the case of diffuse scattering the difference between resulting intensities is immense, while for the Bragg intensities it is much smaller. This sensitivity of diffuse scattering could potentially be used to improve the description of the average structure.